2003
DOI: 10.1152/ajpheart.00625.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and high glucose upregulate AT1receptor expression and potentiate ANG II-induced proliferation in VSM cells

Abstract: We examined the effect of hypoxia and high glucose (HG) on ANG II type 1 (AT 1) receptor expression and proliferation in cultured vascular smooth muscle (VSM) cells. Exposure of quiescent cells to hypoxia in a serum-free DME-Ham's F-12 medium for 6-24 h induced a progressive increase in AT 1 mRNA expression. Exposure of cells to 24 h of hypoxia also resulted in a significant increase in ANG II receptor binding as assessed with 125 I-labeled ANG II. Treatment with ANG II (1 M) for 24 h under normoxic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
46
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 52 publications
7
46
1
1
Order By: Relevance
“…22,23 The AT 1 receptor is a G protein-coupled receptor that mediates most of the known biologic effects of Ang II. Both local production of Ang II and AT 1 receptor expression are significantly increased in cardiac myocytes and vessels in streptozotocin-induced diabetic rats 24 and in vascular smooth muscle cells exposed to high glucose levels, 25 which are consistent with our findings. Activation of the AT 1 receptor might 'turn on" NADPH oxidase and consequently enhance ROS, such as superoxide anion, which can react with nitric oxide, leading to its inactivation by producing peroxynitrite.…”
Section: Discussionsupporting
confidence: 91%
“…22,23 The AT 1 receptor is a G protein-coupled receptor that mediates most of the known biologic effects of Ang II. Both local production of Ang II and AT 1 receptor expression are significantly increased in cardiac myocytes and vessels in streptozotocin-induced diabetic rats 24 and in vascular smooth muscle cells exposed to high glucose levels, 25 which are consistent with our findings. Activation of the AT 1 receptor might 'turn on" NADPH oxidase and consequently enhance ROS, such as superoxide anion, which can react with nitric oxide, leading to its inactivation by producing peroxynitrite.…”
Section: Discussionsupporting
confidence: 91%
“…7 It was also reported that AT 1 R mRNA in VSMCs was upregulated under hypoxia (3% O 2 , 24 hours). 32 However, in the present study, both AT 1 R mRNA and protein were downregulated under hypoxia (1% O 2 , 24 hours). Although it is possible that the different oxygen concentration may affect the result, the reason for this discrepancy between the present study and the previous one is not clear at this time.…”
Section: Discussioncontrasting
confidence: 65%
“…Although it remains unclear whether the subtle constitutive activity of the native AT 1 receptor has a pathophysiological role, the enhancement of its constitutive activity olmesartan Inverse agonist activity of olmesartan Y Qin et al through upregulation of receptor expression may promote cardiovascular remodeling. Indeed, the expression level of the AT 1 receptor in vascular cells is upregulated by low-density lipoprotein cholesterol, 13 insulin, 14 glucose, 15 progesterone 16 and inflammatory cytokines, such as interleukin-1a or interleukin-6. 17,18 Analyses of the binding affinity of olmesartan for mutant AT 1 receptors as well as molecular modeling analyses indicated that the ternary interactions between the hydroxyl group and Tyr 113 and between the carboxyl group and Lys 199 and His 256 are critical to the inverse agonist properties of olmesartan, but that the interaction between the tetrazole group and Gln 257 is dispensable.…”
Section: Discussionmentioning
confidence: 99%